DASAR - DASAR ILMU DAN HAKIKAT PENDIDIKAN DALAM PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM - Muhammad Yusron Maulana El-Yunusi; Fitri Aulia Rahma; Najma Alyaa Kamilah; Muhammad Rafli Imansyah (Hijri, 2025)
This article explores the principles of science and the foundations of education from the perspective of Islamic educational philosophy using a literature review method. Islamic education is considered not merely the transmission of knowledge, but also a comprehensive effort to develop an individual's character as a whole. From an Islamic perspective, knowledge plays a significant role, not only as a tool to fulfill intellectual needs but also as a way to draw closer to Allah SWT and create a civilized society. Research findings indicate that Islamic education emphasizes the balance between spiritual, moral, and intellectual aspects, making Islamic educational philosophy the primary foundation for facing the challenges of the modern era and simultaneously producing a generation that is knowledgeable, virtuous, and capable of making a positive contribution to social life.